2016
DOI: 10.1002/clen.201400639
|View full text |Cite
|
Sign up to set email alerts
|

Bioinoculants and Vermicompost ImproveOcimum basilicumYield and Soil Health in a Sustainable Production System

Abstract: With respect to the adverse effects of chemical fertilizers on the environment and their higher cost, an alternative method of improving soil fertility has been tested. Application of vermicompost (VC) (produced from de-oiled waste) along with efficient bioinoculants (nitrogen fixer: Bacillus sp., JN700924; phosphate solubilizer: Bacillus megaterium, ATCC 14581; plant growth promoter: Pseudomonas monteilii, HQ 995498; arbuscular mycorrhizal fungus (AMF): Glomus intraradices) in different combinations were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…The low carbon content (Table 1) indicates low levels of organic matter in the soil. Thus, the addition of HS would be an important practice to stimulate the growth of basil (Verma et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The low carbon content (Table 1) indicates low levels of organic matter in the soil. Thus, the addition of HS would be an important practice to stimulate the growth of basil (Verma et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Tiwari et al (2017) co-inoculated the AMF Glomus aggregatum and the fungus Trichoderma harzanium in basil and concluded that this interaction can reduce the negative effects of nematodes and, at the same time, increase plant growth and EO production. In another study with basil, inoculation with the AMF Glomus intraradices and humic substance (HS) addition (as vermicomposting) also increased the plant growth by 56% and the EO production by up to 48% (Verma et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations